Experimental Approaches to Neutrino Nuclear Responses for ββ Decays and Astro-Neutrinos - Ejiri, Hiroyasu (Frontiers in Physics, 2021)
Fundamental properties of neutrinos are investigated by studying double beta decays (ββ-decays), while atro-neutrino nucleo-syntheses and astro-neutrino productions are investigated by studying inverse beta decays (inverse β-decays) induced by astro-neutrinos. Neutrino nuclear responses for these ββ and β-decays are crucial for these neutrino studies in nuclei. This reports briefly perspectives on experimental studies of neutrino nuclear responses (square of nuclear matrix element) for ββ-decays and astro-neutrinos by using nuclear and leptonic (muon) charge-exchange reactions